Budaya dalam Agenda 2030: Upaya dalam Mewujudkan Sustainable Development Goals di Kota Pekalongan - Endah Tarwiyani Yuniar; Rr. Hermini Susiatiningsih; Fendy Eko Wahyudi (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
UNESCO as an official UN agency, contributes to the successful implementation of the development agenda known as the SDGs through one of its programs, UNESCO Creative Cities Network (UCCN). Pekalongan as a member of UCCN is required to be able to create a creative city that can support the achievement of the SDGs. This study is aimed at how the Pekalongan City Government, as a member of the UCCN, is working to achieve the SDGs through Pekalongan Batik culture according to the UCCN framework through the concept of sustainable development. Furthermore, this study will also analyze the behavior of the Pekalongan City Government towards UCCN cooperation using three compliance indicators, namely output, outcome, and impact. This research uses a qualitative descriptive approach with sources obtained from interviews and literature studies and analyzed using content analysis techniques. he findings of this study show that the Pekalongan City Government has implemented the UCCN mandate to make culture an important component in achieving the SDGs by involving people from all backgrounds of life. . By making batik as a driving force in achieving the SDGs, batik production in Pekalongan City can also have good resilience during a crisis.